2021
DOI: 10.3390/biomedicines9020194
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the PD-1/PD-L1 Axis for Malignant Transformation and Risk Assessment of Oral Leukoplakia

Abstract: Background: The programmed cell death ligand 1/programmed cell death receptor 1 (PD-L1/PD-1) Immune Checkpoint is an important modulator of the immune response. Overexpression of the receptor and its ligands is involved in immunosuppression and the failure of an immune response against tumor cells. PD-1/PD-L1 overexpression in oral squamous cell carcinoma (OSCC) compared to healthy oral mucosa (NOM) has already been demonstrated. However, little is known about its expression in oral precancerous lesions like o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 54 publications
1
29
0
Order By: Relevance
“…The immune checkpoint regulator PD-L1 is minimally expressed in normal oral epithelium but is expressed in a proportion of dysplastic epithelium either independent of dysplasia grade (Chen et al, 2019;Dave et al, 2020;Gonçalves et al, 2017) or increased with increasing grade (Ries et al, 2021;Sieviläinen et al, 2018) and proportional to CD8+ lymphocyte density in the infiltrate (Chen et al, 2019). Analysis and interpretation is complex, but expression has been claimed to be greater in dysplasias preceding malignant transformation than those not-progressing (Dave et al, 2020;Ries et al, 2021).…”
Section: Dys Pl a S Ia With LI Chenoid Immune Re S P Ons Ementioning
confidence: 99%
See 1 more Smart Citation
“…The immune checkpoint regulator PD-L1 is minimally expressed in normal oral epithelium but is expressed in a proportion of dysplastic epithelium either independent of dysplasia grade (Chen et al, 2019;Dave et al, 2020;Gonçalves et al, 2017) or increased with increasing grade (Ries et al, 2021;Sieviläinen et al, 2018) and proportional to CD8+ lymphocyte density in the infiltrate (Chen et al, 2019). Analysis and interpretation is complex, but expression has been claimed to be greater in dysplasias preceding malignant transformation than those not-progressing (Dave et al, 2020;Ries et al, 2021).…”
Section: Dys Pl a S Ia With LI Chenoid Immune Re S P Ons Ementioning
confidence: 99%
“…The immune checkpoint regulator PD-L1 is minimally expressed in normal oral epithelium but is expressed in a proportion of dysplastic epithelium either independent of dysplasia grade (Chen et al, 2019;Dave et al, 2020;Gonçalves et al, 2017) or increased with increasing grade (Ries et al, 2021;Sieviläinen et al, 2018) and proportional to CD8+ lymphocyte density in the infiltrate (Chen et al, 2019). Analysis and interpretation is complex, but expression has been claimed to be greater in dysplasias preceding malignant transformation than those not-progressing (Dave et al, 2020;Ries et al, 2021). However, the immune environment of dysplasia is complex and other mechanisms underlie immune surveillance including epithelial dendritic cells (Öhman et al, 2012;Pellicioli et al, 2017;Souto et al, 2018) and the frequent mutation of p53, which downregulates the innate immune response and inhibits immune surveillance (Ghosh et al, 2021).…”
Section: Dys Pl a S Ia With LI Chenoid Immune Re S P Ons Ementioning
confidence: 99%
“…11], which is common among leukoplakia biopsies and may also harbor malignant potential (12); as prior molecular studies suggest genetic overlap between KUS and dysplasia includes frequent alterations in TP and KMTC (13). In addition, several preclinical studies have reported increased expression of programmed cell death receptor 1 (PD-1) ligand (PD-L1), on leukoplakic lesions with higher degrees of dysplasia (14)(15)(16), suggesting that immune escape may serve as a key mechanism for malignant transformation to oral carcinoma. To that end, we are currently accruing to a clinical trial of the PD-1 inhibitor nivolumab as preventative immunotherapy in high-risk oral leukoplakia, namely PVL or proliferative leukoplakia (NCT03692325).…”
Section: Introductionmentioning
confidence: 99%
“…To show the relative change in expression rates, the fold change is used. A fold change of 2 means that the expression has doubled (28).…”
Section: Laboratory Examinationmentioning
confidence: 99%